Muito mais do que pe(n)sam : percepções e experiências acerca da obesidade entre usuárias da rede pública de saúde do município Fortaleza-Ceará - Pinto, Maria Soraia (2009)
The obesity is a complex phenomenon that occurs in an important parcel of the world-wide population, in special in the adult women of lower incomes. The obesity also can be seen as a physical attribute, perceived, interpreted and influenced for the social system. The aim of this study was to understand the perceptions and experiences of women attended in a health family center of the city of Fortaleza with obesity diagnosis. This is study is about a qualitative inquiry with phenomenologic-hermeneutic approach, whose adopted methodology strategy was the joint enters the interviews in depth and the free comment. 8 interviews with women between 28 and 56 years had been carried through, with average of age of 44 years. All presented obesity degree II (BMI= 35,0-39,9kg/m2), and had related the experience with the excess of weight at least for 5 years, moreover they presented hypertension, diabetes, dyslipidemia and osteomuscular problems, the majority was married,house owner and had children. The average of family remuneration was 1-2 minimum wages. The education level was between secondary education and the incomplete fundamental education. The categorization of the empirical material indicated four thematic axles, and from which the axles had been tracings analysis central offices. 1) Body Self-perception ; 2)Etnoethyology of the obesity; 3) Stigma and the Repercussions in the distinct spheres of the life; 4) Treading the Ways of the Cure. Each thematic axle was unfolded in different dimensions. The results had disclosed that the women perceive her excess weight, however they are not classified as obese. The medicine use, the feeding and important moments of life had been considered basic for the explanation of the profile of obesity in the group. Under the women “weigh” stigma and discriminations attributed by their appearance. Finally for the deponents the obesity is an illness that has cure. In this direction, the study it calls attention for importance the multidimensionality of the obesity. Such understanding is basic for the proposal of plans and strategies of attendance in the field of the health politics.